Blockchain-Enabled Secure Data Aggregation Routing (BSDAR) Protocol for IoT-Integrated Next-Generation Sensor Networks for Enhanced Security - N. Vidhya; C. Meenakshi (International Journal of Computational and Experimental Science and Engineering, 2025)
WSNs, due to their special characteristics as compared to conventional networks, have become the focus of extensive research. A large-scale IoT forms the backbone of billions of resource-constrained next-generation sensors interconnected with each other. Their large-scale deployments remain one of the most serious challenges to existing security mechanisms due to the dynamic characteristics of IoT devices, which could not provide efficient protection against malicious adversaries. Besides, conventional routing protocols are vulnerable to various security threats from the unreliability and open-access nature of the internet. This research article presents a novel blockchain-enabled secure data aggregation model protocol for routing in IoT-integrated next-generation networks using sensor nodes. The BSDAR protocol is capable of improving energy routing performance while ensuring strong node-level data shield against malicious attacks. It first organizes the networking nodal points into autonomous clusters of different radii to effectively avoid energy holes around the BS. Then, the protocol uses the A-star based heuristics strategy to construct well-organized and non-looping routing paths. The BSDAR protocol has integrated blockchain technology with the goal of ensuring the security of the data communication process. In that, end-to-end communication is preserved by a decentralized and tamper-proof approach against malicious nodes. The simulation results prove that BSDAR significantly outperforms existing solutions in energy consumption, throughput, network lifetime and time complexity, thus presenting a promising solution for secure and scalable IoT deployments.